2023
DOI: 10.3390/cancers15020495
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Study of the Benefit of Concomitant Radiotherapy with Cemiplimab in Advanced Cutaneous Squamous Cell Carcinoma (cSCC): A Retrospective Cohort Study

Abstract: Background: Cemiplimab is a monoclonal antibody targeting the PD-1, and phase II trials have shown its efficacy in the treatment of advanced cutaneous squamous cell carcinoma in patients who are not candidates for curative surgery or radiation therapy as a first- or later-line treatment. A synergistic antitumoral response has been demonstrated with concurrent radiotherapy and PD1-immunotherapy. However, no real-life study has demonstrated this effect in advanced cutaneous squamous cell carcinoma. Methods: We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, the combination therapy group demonstrated an earlier radiologic disease response, with a median duration of 3 months (versus 5.5 months in the monotherapy group) and a prolonged treatment response even after discontinuation of PD-1 blockade. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the combination therapy group demonstrated an earlier radiologic disease response, with a median duration of 3 months (versus 5.5 months in the monotherapy group) and a prolonged treatment response even after discontinuation of PD-1 blockade. 26 …”
Section: Resultsmentioning
confidence: 99%
“…However, the combination therapy group demonstrated an earlier radiologic disease response, with a median duration of 3 months (versus 5.5 months in the monotherapy group) and a prolonged treatment response even after discontinuation of PD-1 blockade. 26 Several studies evaluated unique scenarios, such as the use of cemiplimab to treat periorbital CSCC, CSCC with large caliber PNI, and CSCC in SOTRs. For periorbital CSCC, treatment with cemiplimab resulted in response rates between 82% and 100% and negated the need for orbital exenteration in most cases.…”
Section: Real World Efficacy Datamentioning
confidence: 99%
“…In this study, the observed objective response rate was 47.6 in Cemiplimab consumption versus 41.6 in combined treatment. The simultaneous use of radiotherapy and Cemiplimab (3 months) caused a faster clinical‐radiological response than the use of Cemiplimab alone (5.5 months) 157 …”
Section: Checkpoint Inhibitorsmentioning
confidence: 98%
“…The simultaneous use of radiotherapy and Cemiplimab (3 months) caused a faster clinical‐radiological response than the use of Cemiplimab alone (5.5 months). 157 …”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…Cemiplimab, a monoclonal antibody targeting the programmed death 1 (PD-1) receptor, has exhibited substantial potential in the management of advanced SCC [ 5 ]. However, the real-world effectiveness of this therapeutic agent, especially within distinct patient populations and varied clinical scenarios, remains a subject of paramount interest [ 6 ].…”
Section: Introductionmentioning
confidence: 99%